Аnalysis of the impact of distribution of contradictions of trade and small business enterprise on multiplicable tax budget receipts (Economics and region, 2018)
Today, all leading Ukrainian economists and politicians talk about the need for small enterprises to become the main driving force behind Ukraine's exit from the global economic crisis and the development of a developed market economy in our country. But in practice, under the guise of small businesses, trade associations or individual business entities are registered for the purpose of trade and taxation under the simplified system that exists for small enterprises in Ukraine. But in reality, trade does not correspond to the essence and definition of entrepreneurial activity. Therefore, we consider it necessary to differentiate between the concept of entrepreneurial activity and trade at the legislative level. The purpose of the study is to substantiate the expediency of differentiating the concepts of trade and entrepreneurship from the legal level, and to prove, on the basis of the construction of an appropriate analytical model, the expediency of abolishing preferential taxation for traders and their transition to the general system of taxation. In Ukraine, the small business sector is now well developed. Trade occupies a leading role in the structure of small enterprises of our state. Due to the effect of preferential taxation, business entities occupied in the commercial sphere receive significant speculative profits, which in the conditions of the crisis are not permissible and leads to a lack of a significant amount of financial resources by the state budget of Ukraine. Therefore, in our opinion, it is necessary to distinguish at the legislative level the notions of trade and small business, in order to increase tax revenues to the budget from the subjects of trade activity. We analyzed the influence of this solution on the economy with the help of the most modern method of modeling economic systems - the method of automatic modeling. The developed model allows us to trace the impact of this decision in time in both the short and long-term, is adapted to the economic and socio-political realities of Ukraine, takes into account the majority of economic and social risks associated with the introduction of the proposed approach to taxation of business entities in the field of trade.
Keywords: small enterprise; trade; automaton model; automaton modeling method; tax rate; taxation; analysis; budget; revenue